The relationship between a costume prop and a toddler’s type and intensity of movement and social participation - Cleary, Megan Lynn (Kansas State University, 2012)
With obesity on the rise in young children, the need to examine interventions to increase activity levels, a factor in obesity, in childhood is apparent. The purpose of this study was to examine the relationship between toddlers wearing a costume prop and their type and intensity of movement as well as their level of social participation. It was hypothesized that intensity of movement and types of movement would increase when the child wore a cape compared to no cape. A total of fifty-four subjects between the ages of 24 and 36 months participated in the study, structured into an intervention group (n = 27) and a control group (n = 27). Toddlers in the control group were observed for 20 minutes during free play inside the classroom wearing a specifically designed data collection garment (which looked like a “vest”) to record movement and sound. Participants in the intervention group were observed with the same data collection garment and the costume prop “cape” for 20 minutes during morning free-play period inside. The toddlers‟ behaviors were coded as outlined by Brown, Pfeiffer, McIver, Dowda, Joao, Almeida, and Pate‟s (2006) Observational System for Recording Physical Activity in Children-Preschool (OSRAC-P), modified to capture the unique movements of toddlers for the present study. Analysis of Variance (ANOVA) and a Multivariate Analysis of Variance (MANOVA) were utilized to examine the effect of a costume prop on intensity of activity, types of gross motor movement, and forms of social play. Results revealed the intervention group exhibited significantly greater engagement in onlooker, solitary, and parallel play (p < .001) than the control group. No significant differences in the levels of intensity or types of activity exhibited between the two groups. Implications for further research on physical activity and stimulating physical activity in the classroom are discussed
Keywords: Toddlers; Play; Social participation; Physical activity; Costume prop; Design (0389); Early Childhood Education (0518); Physical Education (0523)